2003
DOI: 10.1007/s00424-003-1032-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically induced potentials in atrial fibroblasts from rat hearts are sensitive to hypoxia/reoxygenation

Abstract: Membrane potential changes of atrial fibroblasts in response to mechanical stress have been considered to modulate the rhythmic electrical activity of healthy hearts. Our recent findings suggest that cardiac arrhythmia after infarction is related to enhanced susceptibility of the fibroblasts to physical stretch. In this study, we analysed the effect of hypoxia/reoxygenation, which are major components of tissue ischemia/reperfusion, on the membrane potential of atrial fibroblasts. Intracellular microelectrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…This current reversed at about −20 mV, which coincided with the resting potentials of the control fibroblasts and of those exposed to hypoxia, and also with those reported previously in rat cardiac fibroblasts (12). The reversal potential of −20 mV suggested a possibility of Cl − channels or a nonselective cation channel.…”
Section: Discussionsupporting
confidence: 89%
“…This current reversed at about −20 mV, which coincided with the resting potentials of the control fibroblasts and of those exposed to hypoxia, and also with those reported previously in rat cardiac fibroblasts (12). The reversal potential of −20 mV suggested a possibility of Cl − channels or a nonselective cation channel.…”
Section: Discussionsupporting
confidence: 89%
“…Other factors potentially involved in the induction or maintenance of AF include inflammation, autonomic nervous system activity, atrial ischemia, 154 atrial dilation, 155 anisotropic conduction, 156 and structural changes associated with aging. 3 It has been postulated that oxidative stress and inflammation may be involved in the genesis of AF.…”
Section: Other Factors Contributing To Atrial Fibrillationmentioning
confidence: 99%
“…Recently, it was reported that rat ventricular fibroblasts possess an inward rectifier K+ current (I Kir ) and a delayed rectifier K+ current (I Kr )(Chilton et al, 2005; Rose et al, 2007; Shibukawa et al, 2005). In addition, human cardiac fibroblasts were shown to express calcium-activated big conductance potassium channels (BK Ca )(Wang et al, 2006), as well as additional nonselective channels (Du et al, 2010; El Chemaly et al, 2006; Kamkin et al, 2003a; Kamkin et al, 2005; Kamkin et al, 2003b; Ma et al, 2008; Rose et al, 2007). In addition, recent studies have indicated fibroblasts isolated from normal hearts and maintained in culture express ATP-sensitive K+ channel (K ATP ) subunits (Benamer et al, 2013; Chilton et al, 2005).…”
Section: Introductionmentioning
confidence: 99%